PEDAGOGICAL FOUNDATIONS FOR DEVELOPING A READING CULTURE IN CHILDREN - Muxabbat Jurayevna Maxmudova (Modern American Journals, 2025)
The article analyzes the role of books in the moral, aesthetic, and intellectual development of children. It presents methodological approaches to the use of fiction in enriching the spiritual world of preschool-aged children. The paper also explores ways to cultivate a love for books through the collaboration between families and educational institutions.
Keywords: Reading culture, preschool children, fiction, moral education, aesthetic taste, creative activity, national values.